Establishment of the benchmarking tool for evaluating the operation of biorepositories for pathogenic resource using a modified Delphi method - Geng Hong; Dongxin Liu; Yuanyuan Zhao; Yalin Zhai; Fengzekuan Zhao; Yanhai Wang; Mengnan Jiang; Qiang Wei (Elsevier, 2024)
In recent years, as the infectious diseases caused by pathogens such as novel coronavirus and mpox (formerly called monkeypox) spread globally, the significance of identification, preservation, and sharing of pathogenic resources become prominent. Along with the rapid development of biorepositories, it is imperative to evaluate their operation in a scientific manner. By using the literature review and modified Delphi method, this study develops a benchmarking tool for the comprehensive evaluation of the operation of biorepositories for pathogenic resources. The effective response rates of both rounds of expert surveys were 100 %. The authority coefficients (Cr) were 0.82 and 0.85, respectively, manifesting the reliability of consultation results. In the second-round survey, the Kendall's coefficient of concordance (Kendall's W) of all indicators ranged from 0.09 to 0.31 (P < 0.001), the comprehensive score ranged from 4.02 to 4.94, the standard deviation ranged from 0.21 to 0.77, and the coefficient of variation (CV) ranged from 0.04 to 0.22, indicating that the expert opinions reached consensus. The final benchmarking tool was composed of 4 primary indicators, 12 secondary indicators, and 65 tertiary indicators. The weights of the four primary indicators allocated through the rank-sum ratio method, namely organizational structure, management requirements, biobanking capacity, and sharing capacity, were 30.50 %, 30.08 %, 25.45 %, and 13.97 %, respectively. The benchmarking tool established in this study provides references for the comprehensive evaluation of the operation and puts forward advice for the sustainable development of biorepositories for pathogenic resources.